A review of eDNA technology in avian monitoring: Current status, challenges and future perspectives - Ying Ke; Tong Liu; Chenglong Han; Xue Yu; Jinmei Wang; Laixing Ding; Hongliang Pan; Xunqiang Mo; Xueqiang Lu (Avian Research)
In recent years, environmental DNA (eDNA) has garnered significant attention as a novel tool in biodiversity monitoring, recognized for its efficiency, convenience, and non-invasiveness. Despite its extensive application in various ecological studies, such as conservation, invasion biology, biomonitoring and biodiversity survey assessment, its use in avian monitoring remains in its infancy. This review critically examines the potential and limitations of eDNA technology for avian monitoring, focusing on current advancements and ongoing challenges in this emerging field. Water and air are the primary environmental media for collecting avian eDNA, although other sources like spider webs and plant flowers have been explored as well. Notably, airborne eDNA has been reported to capture the highest diversity of avian species. While avian eDNA technology has shown promise for monitoring rare and endangered species and assessing avian diversity, significant challenges remain, particularly in sampling strategies, DNA extraction methodology, primer selection, and ascertain abundance. Additionally, we discussed the factors influencing the production, transportation, and degradation of avian eDNA in the environment. Finally, we suggested future research directions, including optimizing sampling strategies, developing avian-specific universal primers, expanding avian DNA barcode databases, enhancing eDNA detectability, and integrating environmental RNA (eRNA) and eDNA approaches.